"Spirit and Power": Modernity on Miracles, Biblical Studies and the Leap of Faith - Giambrone, Anthony (Teologia w Polsce, 2020)
Modern interpretation of the Holy Scripture, especially historicocritical exegesis must crash with the classical dogmatic approach. The case in which this crash is unavoidable is the historicity of Jesus Christ and his miraculous deeds. For contemporary mentality miracles are definitely strange so it is not surprising that such kind of interpretation of the Gospels, in which miracles taken literally are excluded, has been occurring for few ages now. Today, we see a debate between exegetes who are deeply engaged in modern rationalistic paradigm and the ones who try to be faithful to the Church testimony in the first place. This article argues that modern exegesis must lead to the leap of faith. Only faith can affirm the truth of the Gospel, taking aside the question of historical character of Jesus’ miracles. Ultimately, the case of Jesus is mainly about faith, not only about historical research.